Beyond the crisis: EMU and labour market reform pressures in good and bad times - Vassilis Monastiriotis; Sotirios Zartaloudis (London School of Economics and Political Science (LSE), European Institute, 2010)
There is a widespread perception among the public and policy-makers that EMU carries one-way pressures for enhanced flexibility in the labour market. We discuss the theoretical basis of this by examining four mechanisms through which the establishment of the common currency and the functioning of EMU can impact on the labour markets, both within the Eurozone and of the New Member States. We argue that the theory and empirics of the link between EMU and labour market flexibility are not conclusive, leaving room for varying degrees of, and directions for, the (de)regulation of national labour markets. This discretion is partly reflected in the experience of labour market reforms in the Eurozone. An examination of the institutional framework for employment policies in the EU further corroborates the conclusion that EMU does not restrict, but rather puts on the agenda, the active exploration of policy options aimed at strengthening the resilience and adaptability of the European economy as well as its quality, fairness and competitiveness. We argue that this is no different today, during or after the crisis, than it was 'before it all started'.
Keywords: 330